Combined effects of radiation and heat generation on MHD natural convection flow along a vertical flat plate in presence of heat conduction - Ali, Mohammad Mokaddes; Akhter, Rowsanara (BRAC University, 2010)
Study of the effects of radiation and heat generation on MHD natural convection flow of an incompressible viscous electrically conducting fluid along a vertically placed flat plate in presence of heat conduction is considered. The governing equations of the flow are transformed into dimensionless from with appropriate transformations and then solved using the implicit finite difference method with Keller-Box scheme. The resulting numerical solutions of transformed governing equations are presented graphically in terms of velocity profile, temperature distribution, local shear stress, local heat transfer rate and surface temperature and the effects of magnetic parameter (M), radiation parameter (R), Prandtl number(Pr) and heat generation parameter (Q) on the flow and the graphs are discussed.